(untitled) (Nusantara Medical Science Journal, 2018)
Background: Intrauterine growth restriction (IUGR) is still a major cause of perinatal morbidity and mortality. IUGR incidence ranged from 4.4 to 6.44% of pregnant women. Human Leukocyte Antigen - E and NK cells are thought to play an important role towards the process of IUGR. Objective: To determine aetiopathogenesis HLA-E expression and NK Cell in IUGR. Methods: An analytical observational study conducted through a cross-sectional approach. The research was conducted on March-October 2015 at the Obstetrics and Gynecology Department, Dr. Moewardi Hospital Surakarta and at of Laboratory of Pathology, Faculty of Medicine, Universitas Sebelas Maret Surakarta. Subjects who meet the inclusion and exclusion criteria consisted of 20 patients with IUGR and 20 normal pregnant patient. The researcher examined HLA-E Expression and NK cells in trophoblast using immunohistochemical method and statistical analysis using t test. Results: The average HLA-E expression in the trophoblast in IUGR group 17.80 ± 5.55, compared with normal pregnancy 66.23 ± 19.83, p value = 0.0001 (p <0.05). The average expression of NK cells in trophoblast in IUGR group 137.71 ± 28.09 compared with normal pregnancy 31.75 ± 14.77, p value = 0.0001 (p <0.05). Conclusion: HLA-E expression in normal pregnancy trophoblast is higher than pregnancies with IUGR. Expression of NK cells in pregnancy with IUGR is higher compared with normal pregnancy.